Cognitive Function Is Associated With Multiple Indices of Adiposity in the Canadian Longitudinal Study on Aging: A Cross-Sectional Analysis. Issue 7 (28th June 2022) - Sakib, Mohammad Nazmus; Ramezan, Reza; Thompson, Mary E.; Best, John R.; Hall, Peter A.
ABSTRACT: Objective: Prior studies have suggested reciprocal relationships between cognitive function and adiposity, but this has not been investigated with population representative data sets. The purpose of this study was to examine the association between cognitive function and adiposity in a large population-based sample of middle-aged and older adults. It was hypothesized that better scores on tests of cognitive function would be associated with lower adiposity, and this association would be primarily mediated through life-style behavior and physical health status. Methods: Using baseline data from the Canadian Longitudinal Study on Aging ( N = 30, 097), we tested our hypotheses using three indicators of cognitive function (animal fluency, Stroop interference, and reaction time) and four indicators of adiposity (body mass index, total fat mass, waist circumference, and waist-hip ratio). Hierarchical multivariable linear regression modeling was conducted followed by tests for moderation by socioeconomic status and mediation through diet, physical activity, hypertension, and diabetes status. Results: All measures of cognitive indicators were significantly associated with adiposity after adjusting for confounders. In general, superior performance on animal fluency, Stroop, and reaction time tasks were associated with lower adiposity by most metrics. Stroop interference was associated with lower adiposity across all metrics, including body mass index ( b = − 0.04, 95 % confidence interval [CI] = − 0.06  to − 0.01), total fat mass ( b = 19.35, 95 % CI = 8.57  to 30.12), waist circumference ( b = 33.83, 95 % CI = 10.08  to 57.58), and waist-hip ratio ( b = 0.13, 95 % CI = 0.01  to 0.24). These associations were more substantial for moderate- and high-income subpopulations. Mediation analyses suggested that the aforementioned effects were mediated through life-style behavior (e.g., diet and physical activity) and physical health conditions (e.g., diabetes and hypertension). Conclusions: Reliable associations exist between cognitive function and adiposity in middle-aged and older adults. The associations seem to be mediated through life-style behavior and physical health conditions.